Religion, Ethics and the Meaning of Life (KEMANUSIAAN The Asian Journal of Humanities, 2008)
Religion as a concept has generated some nuances that retain the sense of religiosity or spirituality while negating the idea of a personal anthropomorphic deity. One should therefore be clear as to the usage of this concept in a given context. While religion, ethics, and the meaning of life are intertwined, there are now variants wherein nonbelievers can themselves be ethical and lead meaningful lives. The author believes that the discarded theistic deity can be redeemed and given a reinterpretation that is suitable to our contemporary postmodern setting.